The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/1319-2442.124459
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thymocyte globulin versus basiliximab induction in renal transplant recipients: Long-term outcome

Abstract: Although basiliximab and rabbit anti-thymocyte globulin (ATG) are effective in delaying and reducing the incidence of acute rejection (AR) thus improving short-term graft survival, their impact on long-term graft survival has not been well established in renal transplant recipients. To evaluate the long-term efficacy after induction therapy with ATG/basiliximab in renal transplant recipients, we studied retrospectively 86 renal transplant recipients of living donor renal transplantation from 2003 to 2006; of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…This includes the effects of CMV infection and Valganciclovir used for prophylaxis. This is more than previously done retrospective study in India by Kesiraju et al 4 The rate of bacterial, fungal and viral infections was comparable in both the groups. Similar to Liborio et al 11 The rate of Lower respiratory tract infection was higher in ATG group 15.2% vs. 10.5% in basiliximab group similar to Wang et al 13 The incidence of UTI was similar between the two groups (13.3% vs. 12.5%) in contrast to Huang et al 20 where there was higher incidence of UTI in ATG group.…”
Section: Image 1 Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This includes the effects of CMV infection and Valganciclovir used for prophylaxis. This is more than previously done retrospective study in India by Kesiraju et al 4 The rate of bacterial, fungal and viral infections was comparable in both the groups. Similar to Liborio et al 11 The rate of Lower respiratory tract infection was higher in ATG group 15.2% vs. 10.5% in basiliximab group similar to Wang et al 13 The incidence of UTI was similar between the two groups (13.3% vs. 12.5%) in contrast to Huang et al 20 where there was higher incidence of UTI in ATG group.…”
Section: Image 1 Discussionsupporting
confidence: 57%
“…In contrast to these studies Brennan et al 7 found higher incidence in basiliximab group. The incidence of CMV infection is more in both groups when compared to previous studies Kesiraju et al 4 who used lesser doses of ATG and used CMV prophylaxis in both groups but less than the incidence in Ulrich et al and Kim et al 12,14 There were two previous studies from India Kesiraju et al 4 and Patel et al The death censored graft loss was 3.8% in ATG group and 4.1% in the basiliximab group. Total graft loss was 8.9% in the ATG group and 7.58% in the basiliximab group less than previous studies done in India.…”
Section: Image 1 Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Anti-thymocyte globulin (ATG) induction before transplantation, followed by a triple immunosuppressive regimen (MMF, prednisone, and tacrolimus) post-transplantation is common practice at KAMC. Studies have shown the effectiveness of immunosuppressive therapy, encompassing triple therapy and IL-2 receptor antibody basiliximab in reducing the rates of DGF among kidney recipients, and though the induction used differs from that of KAMC, both ATG and basiliximab are safe and effective options [28]. Triple immunosuppressive therapy and ATG induction were given to all patients in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Incidence of leucopenia and thrombocytopenia in basiliximab-treated renal transplant patients are approximately 10%–15% and 5%, respectively [ 76 ]. Many comparative studies have demonstrated that leucopenia and thrombocytopenia occurred less in basiliximab [ 64 , 76 , 141 , 147 , 148 ] when compared to other agents used in induction. In the 3 C trial, leucopenia was 3.6 times higher in KTR receiving alemtuzumab as compared to basiliximab [ 147 ].…”
Section: Insight Into Etiology Of Hematological Cytopenia and Subsmentioning
confidence: 99%